Associations between systemic inflammation indicators and nonalcoholic fatty liver disease: evidence from a prospective study - Gong, Hao; He, Qida; Zhu, Lili; Feng, Zhaolong; Sun, Mengtong; Jiang, Jingting; Yuan, Xiaofeng; Shen, Yueping; Di, Jia (Frontiers in Immunology, 2024)
Background: Although inflammation has been linked to nonalcoholic fatty liver disease (NAFLD), most studies have focused only on a single indicator, leading to inconsistent results. Therefore, a large prospective study that includes a variety of welldocumented single and composite indicators of inflammation is needed. This study aimed to thoroughly investigate the potential associations between different systemic inflammatory indicators and NAFLD in the UK Biobank cohort. Methods: After excluding ineligible participants, 378,139 individuals were included in the study. Associations between systemic inflammatory indicators and hepatic steatosis were assessed using multivariate logistic regression. The relationships between systemic inflammatory indicators and nonalcoholic fatty liver disease were analysed using Cox proportional hazards models, and nonlinear associations were investigated using restricted cubic splines. Results: According to the cross-sectional analysis, systemic inflammatory indicators significantly correlated with hepatic steatosis. Over a median follow-up of 13.9 years, 4,145 individuals developed NAFLD. After sufficient adjustment for confounding factors, CRP levels were found to be nonlinearly positively associated with NAFLD risk (P<0.001), representing the strongest correlation among the tested relationships; lymphocyte count and the LMR showed an L-shaped correlation; monocyte count and neutrophil count showed a linear positive correlation (all P< 0.001); and the NLR, PLR, and SII showed a U-shaped correlation (all P<0.001). Conclusions: Multiple systemic inflammatory indicators are strongly associated with the development of NAFLD, and aggressive systemic inflammation management may have a favourable impact on reducing the burden of NAFLD; further randomized controlled studies are needed.